Suspension du droit et rétrécissement du politique : apothéose de l’État planétaire - Jesús Cuenca De la Rosa (Amnis)
The last Golf war could help us to interpret what this beginning of millenium is, better than any other sign. On the utopic (subjective) level, the neoliberal ideologies under American supervisiontend to universalise democracy and human rights everywhere, and simultaneously to settle a market with a planetary dimension. Even a superficial understanding of our concretereality, which would enlighten how the real inhabitants of our world live or survive – what their life of living beings consist in, if we borrow the concept suggested by Michel Foucault in the end of The Will to Know, when he asserts that modernity is caracterized by the intrusion of natural life intothe political field – would inevitably contradict such a noble project. In these conditions, to talk about politics as a contract which freely unites the social practises of the individuals from all countries is a product of fiction.